Can AI Be Too Good to Use? - Fell, Andy (2023)
Much of the discussion around implementing artificial intelligence systems focuses on whether an AI application is “trustworthy”: Does it produce useful, reliable results, free of bias, while ensuring data privacy? But a new paper published Dec. 7 in Frontiers in Artificial Intelligence poses a different question: What if an AI is just too good?
Read_Status: New Read_Status_Date: 2026-01-26T11:33:20.825Z
Keywords: /unread